Unveiling meteorological synergies in the coupling of an abnormal easterly wave and cutoff low in South Africa's February 2023 rainfall - Farahnaz Fazel‐Rastgar; Venkataraman Sivakumar; Masoud Rostami; Bijan Fallah (Meteorological Applications)
Abstract This study seeks to understand the meteorological mechanisms that caused widespread and heavy rainfall from 6 to 14 February 2023, over southern Mozambique and the eastern and northeastern areas in South Africa, including Limpopo Province, Mpumalanga Province and northern KwaZulu‐Natal, by examining different outputs from reanalysis datasets. The heavy rainfall had a substantial hydrological impact, leading to significant flooding and disruptions. This research revealed that a slow‐moving cutoff low (COL) system remained over the central parts of South Africa, triggering extensive and heavy rainfall mostly over the northeastern and eastern provinces. The outcomes from the reanalysis datasets display the influence of the weather system and the interaction between an initiated westerly wave, which converted into a near‐stationary upper‐air cold core upper air COL system, and the easterly wind wave associated with the South Indian Ocean Convergence Zone (SICZ), bringing significant warm humid air from the Indian Ocean into the study area. This study revealed an abnormal structural pattern in the wind vectors, low‐pressure trough, upper and mid‐tropospheric westerly flows and humidity compared with the long‐term climate normal values over Mozambique and the northeastern and eastern regions of southern Africa. This event is exciting from a meteorological perspective due to its intensity and duration, the involvement of cyclonic activity and its implications for understanding the impacts of climate change on weather patterns in southern Africa. The heavy rainfall had a substantial hydrological impact, leading to significant flooding and disruptions, providing valuable data for improving forecasting models and disaster preparedness strategies and underscoring the importance of enhancing climate resilience in regions prone to extreme weather.